2015
DOI: 10.1111/jan.12648
|View full text |Cite
|
Sign up to set email alerts
|

The experience and perceptions of men with prostate cancer and their partners of the CONNECT psychosocial intervention: a qualitative exploration

Abstract: Although there were areas that could be further improved, this psychosocial intervention was valued by the participants. The insight gained from this qualitative exploration can be used to make the necessary changes before the intervention can be tested in a large randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
2
30
0
1
Order By: Relevance
“…This resonates with evidence from previous studies which had successfully used female researchers to interview Caucasian (McCaughan et al, ) and Black (Anderson et al, ) men with CaP. Fergus, Gray, and Fitch () highlighted that most of the male participants in their study expressed preference to be interviewed by a female researcher when they were offered choices between a male or female interviewer.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This resonates with evidence from previous studies which had successfully used female researchers to interview Caucasian (McCaughan et al, ) and Black (Anderson et al, ) men with CaP. Fergus, Gray, and Fitch () highlighted that most of the male participants in their study expressed preference to be interviewed by a female researcher when they were offered choices between a male or female interviewer.…”
Section: Discussionsupporting
confidence: 78%
“…Prostate cancer (CaP) affects one in four Black African (BA) and Black Caribbean (BC) men earlier in life and in more aggressive forms compared with one in eight Caucasian men (Jones & Chinegwundoh, ). However, it appears that access and recruitment barriers may have contributed to the underrepresentation of BA and BC men and their partners in current psychosocial research related to CaP survivors (Bamidele, McGarvey, et al, ) as these have mostly involved Caucasian (McCaughan, McKenna, McSorley, & Parahoo, ; O'Shaughnessy, Ireland, Pelentsov, Thomas, & Esterman, ; Speer, Tucker, McPhillips, & Peters, ) and some African American (AA) (Rivers et al, ) groups.…”
Section: Introductionmentioning
confidence: 99%
“…This study explored the psychosocial experiences of BA/BC men with CaP and their partners in the United Kingdom as they lived through the side effects of CaP treatment within their own sociocultural and marital contexts. Findings indicated that most of the posttreatment experiences of men (eg, feelings of diminished masculinity due to posttreatment sexual dysfunction) and partners (eg, communication barriers to discussing sexual concerns) in this study mirrored previous reports on Caucasian and African‐Americans groups. An intersection of clinical treatment procedures, physical side effects of CaP treatment, and common gender stereotypes regarding masculinity may have contributed to these similarities.…”
Section: Discussionsupporting
confidence: 80%
“…This phenomenon is poorly understood for higher risk BA and BC populations because of their under‐representation in global psychosocial research on CaP survivorship. The majority of studies in this area have predominantly focused on Caucasian groups . The few studies involving Black men have either focused on African‐American or older Jamaican men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation